YOGYAKARIA KOTA PENDIDIKAN DAN EKONOMI ALTERNATIF - Sugiyanto Sugiyanto (LPMPP Universitas Negeri Yogyakarta, 2004)
Yogyakarta is regarded as a city ofeducation, culture, and tourism. However, the government, bureaucracy, stake holders, and king of the acknowledged kingdom of Yogyakarta himself, as head of the Yogyakarta Special Territory, have cautioned everybody to beware that the increasing Realization of the importance ofeducation has brought the city of Yogyakarta to becoming known as the·